2016
DOI: 10.1136/jech-2016-207712
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socioeconomic position on frailty trajectories in 10 European countries: evidence from the Survey of Health, Ageing and Retirement in Europe (2004–2013)

Abstract: Health inequalities due to education, occupational class and wealth tend to persist throughout old age, whereas the negligible effect of income declines with age, which, substantially, highlights the importance of social conditions on the pace of physiological decline in older Europeans and, methodologically, highlights the need to assess multiple measures of socioeconomic position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
107
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 38 publications
15
107
5
2
Order By: Relevance
“…Although these cohort studies have shown that health inequality strongly depends on the context in which individual life courses unfold, cross-national comparative studies of health trajectories remain scarce (Stolz et al 2017). Longitudinal evidence on how education shapes health across the life course is largely limited to the U.S. context.…”
Section: Introductionmentioning
confidence: 99%
“…Although these cohort studies have shown that health inequality strongly depends on the context in which individual life courses unfold, cross-national comparative studies of health trajectories remain scarce (Stolz et al 2017). Longitudinal evidence on how education shapes health across the life course is largely limited to the U.S. context.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies may indicate whether the development of frailty in lower socioeconomic groups will be quicker than that in higher socioeconomic groups throughout later life. So far, two studies have pointed into the direction of persisting (not widening) SEP inequalities in frailty in old age [16,17] .…”
mentioning
confidence: 99%
“…In our study, we found a non-linear, pro- gressive increase of mean frailty levels as people age, which followed a cubic growth pattern with steep increases beginning around the age of 70 years. Such a non-linear growth pattern -with steeper increases among women than men -has been found to be a characteristic for the FI in previous studies of the general older population (e.g., [2,3,5,[7][8][9]11]). It should be noted that there was also a considerable level of individual-level heterogeneity behind these patterns of average frailty levels and increments (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Country was not used as a level, as the proportion of variance on the country-level was limited (see also [8]) and also because the joint model would not converge under a 3-level structure. We first tested the form of the within-person frailty trajectories using age (centred at age 50, divided by 10 years for readability) as the central time variable and found a non-linear, cubic model of change in frailty to provide the best fit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation